Impact of Knowledge Hiding Behaviors on Workplace Invincibility: Mediating Role of Psychological Contract Breach - Wen, Junqi; Zheng, Jiafeng; Ma, Ruijun (Frontiers in Psychology, 2022)
In the recent years, knowledge hiding has gained much popularity in the knowledge management literature. Apart from that, antecedents and consequences of knowledge hiding are being scrutinized at the present time. There have been many studies on the triggering forces of knowledge hiding however; the uncivil behaviors at the workplace have led the organizations and employees in trouble due to its possible associating factors. One such factor that the present study has identified is knowledge hiding behavior at the workplace. This is a quantitative cross sectional study based on the surveys. The population taken in this study is the middle and low level managerial staff of the software houses located in China. The respondents were selected on the basis of convenient random sampling and a sample size of 287 is used in this study. The data collected was employed with the partial least square structural equation modeling using Smart-PLS 3. The findings of the study show that apart from evasive hiding; playing dumb and rationalized hiding play significant role in predicting the workplace incivility. In addition, psychological contract breach has been taken as the mediating variable. The violation of psychological contract among employees can indulge them in negative feelings for each other that may convert to workplace incivility at any available opportunity of revenge. Workplace incivility cannot be completely eradicated from the organizations however; it can be controlled by making relevant policies. The civility among the employees can be attained by due managerial interventions and trainings of the employees considering the protection of victims and due punishment to the perpetrator.